Outcome of Spinal Anesthesia during Emergency Cesarean Section for Severe Preeclampsia and Eclampsia Patients in a Tertiary Care Hospital (Journal of Enam Medical College, 2019)
Background: In Bangladesh eclampsia and severe preeclampsia or toxemia (PET) are the leading cause of perinatal morbidity and mortality. Its management is challenging for the obstetrician and anesthesiologist. Still now general anesthesia is commonly practiced for emergency LUCS in developing countries, but the outcome of spinal anesthesia is better than GA. Recently in developed countries like the UK and United States, spinal anesthesia is also accepted as a safer anesthetic technique.Objective: The objective of our study was to establish spinal anesthesia as a preferable method to reduce maternal and neonatal morbidity and mortality during emergency LUCS in severe PET and eclampsia patients.Materials and Methods: The study was done in the Department of Anesthesiology and ICU of Enam Medical College & Hospital, Savar, Dhaka during the period from January 2016 to December 2017. Total 62 cases of severe PET and eclampsia patients were selected by subarachnoid block for emergency LUCS. Each patient was given magsulph as prophylactic or maintenance dose and judiciously preloaded by crystalloid fluid. Thiopental sodium 50−100 mg was given to those who had convulsion during SAB. About 2−2.5 mL (10−12.5 mg) 0.5% bupivacaine heavy was used by 25−27 G spinocaine in L3−4 or L4−5 space. After the establishment of the desired block, LUCS was performed. Meticulous monitoring was done and all events were recorded and problems were effectively managed.Results: Our study shows higher maternal (96.6%) and neonatal (95.17%) success rate. Almost all patients were eclamptic (74.19%), primi (59.67%), term pregnancy (64.51%), aged between 21–30 years (43.54%) and rest of them had preeclampsia (25.80%), multigravida (40.32%), preterm (35.48%), aged 30 years (30. 64%). Thiopental sodium was given in 9.65% cases for controlling convulsion during LUCS. Remarkable complications were hypotension (33.87%) with highly significant p value (0.000) and bradycardia (27.41%).Conclusion: With close monitoring of perioperative events, spinal anesthesia may be given as a safe alternative technique in severe preeclampsia and eclapmsia rather than GA or epidural even in cases of altered consciousness or restless in presence of an expert and skilled anesthesiologist and thereby perioperative maternal and neonatal morbidity and mortality will be reduced.J Enam Med Col 2019; 9(3): 170-176